2006
DOI: 10.1016/j.jtcvs.2006.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posterior pericardial drainage on the incidence of pericardial effusion after ascending aortic surgery

Abstract: We demonstrated that effective posterior drainage is important to prevent posterior pericardial effusion, and use of a thin drain placed retrocardially appears to be sufficient for these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
0
21
1
1
Order By: Relevance
“…Further more, others have shown that MCT can result in severe postoperative pain and discomfort. [4][5][6][7][8][9][10] Thus, we advocate the use of SCT in patients undergoing open heart surgery. However, these results should be interpreted with caution given the limitations outlined in our discussion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further more, others have shown that MCT can result in severe postoperative pain and discomfort. [4][5][6][7][8][9][10] Thus, we advocate the use of SCT in patients undergoing open heart surgery. However, these results should be interpreted with caution given the limitations outlined in our discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Some have sug gested that the insertion of more than 1 chest tube per patient may exacerbate pain and discomfort, causing a decrease in ambulation that could negatively influence patient outcome. [4][5][6] Currently, no evidencebased guide line exists that dictates whether a single (SCT) or multi ple chest tubes (MCT) should be used. The number of chest tubes inserted is largely left at the discretion of the individual surgeon based on lowlevel evidence or tradi tional practice.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find differences in the types of cardiac valve replacement and the type of prosthesis (mechanic or biologic). Some authors have shown that aortic root and aortic aneurysm surgery are independent risk factors for the development of significant postoperative PE due to prolonged cardiopulmonary bypass and extensive dissection of the heart and the aorta 4,13,14 . In this study, we analyzed the combination of aortic root with cardiac valve replacement, but we did not find a higher risk to develop moderate-to-severe PE in this subgroup.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…More specifically, with the placement of pleural drainage catheters and temporary pacing leads at the end of a procedure, the addition of a catheter leading into the pericardium is sometimes included [74]. This catheter, whether through the main lumen or a second lumen, could hypothetically allow for continued access to the pericardial space and delivery of appropriate antiarrhythmic, antibiotic, or other therapies to the myocardium.…”
Section: Protocolsmentioning
confidence: 99%